Selecting Achievement-Based Students Using Blockchain and AHP: Semarang University Case Study - Hadi, Soiful; Putri, Astrid Novita; Buana, Pratama Angga (Journal of Information System and Informatics, 2024)
The current learning process requires students to be active, creative, and innovative both in activities and lectures. Students are one of the main indicators in the accreditation of a university. Therefore, a tertiary institution is also required to be able to receive and provide assistance to students and graduates in the form of scholarships, such as achievement scholarships. At present, it is quite difficult to determine students who have excelled at tertiary institutions in considering and determining students who are entitled and appropriate to receive them. The Decision Support System is a solution to be able to assist in managing student achievement data and determining the right scholarship recipients, and is supported by blockchain technology so that security is guaranteed and protected so that it is not easily hacked and information can be tracked by parties who are given access, so that they can share information transparently. This study uses the waterfall system development method with the Analytcal Hierarchy Process (AHP) problem solving method for the analysis model of the decision support system , blockchain algorithms, and open source software used solidity ethreum. The actual results will be that a decision support system with the AHP model combined with Blockchain can help provide more precise decisions to determine more appropriate scholarship recipient students, as well as increase trust in parties in tracking every transaction information on student achievement activities transparently and safely.